2018
DOI: 10.1093/mnras/sty2409
|View full text |Cite
|
Sign up to set email alerts
|

Effects of non-Kozai mutual inclinations on two-planet system stability through all phases of stellar evolution

Abstract: Previous full-lifetime simulations of single-star multi-planet systems across all phases of stellar evolution have predominately assumed coplanar or nearly-coplanar orbits.Here we assess the consequences of this assumption by removing it and exploring the effect of giant branch mass loss on the stability of two-planet systems with small to moderate non-Kozai (< 40 degrees) relative inclinations. We run nearly 10 4 simulations over 14 Gyr for F-star, A-star and B-star planet hosts, incorporating main sequence s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

5
5

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 129 publications
1
26
0
Order By: Relevance
“…This au-scale assumption about where major planets should orbit a white dwarf is well-founded because planets on tight orbits are engulfed by the star during the giant branch phases (Kunitomo et al 2011 Gallet et al 2017;Rao et al 2018;Sun et al 2018). No major planets should exist within about 1-2 au of a white dwarf unless they are perturbed there by other major planets (Debes & Sigurdsson 2002;Veras et al 2013Veras et al , 2016Veras et al , 2018Voyatzis et al 2013;Mustill et al 2014;Veras & Gänsicke 2015;Ronco et al 2020). Indeed, until 2019, no major planets in such tight orbits were detected, despite the discoveries of several minor planets (Vanderburg et al 2015;Manser et al 2019;Vanderbosch et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This au-scale assumption about where major planets should orbit a white dwarf is well-founded because planets on tight orbits are engulfed by the star during the giant branch phases (Kunitomo et al 2011 Gallet et al 2017;Rao et al 2018;Sun et al 2018). No major planets should exist within about 1-2 au of a white dwarf unless they are perturbed there by other major planets (Debes & Sigurdsson 2002;Veras et al 2013Veras et al , 2016Veras et al , 2018Voyatzis et al 2013;Mustill et al 2014;Veras & Gänsicke 2015;Ronco et al 2020). Indeed, until 2019, no major planets in such tight orbits were detected, despite the discoveries of several minor planets (Vanderburg et al 2015;Manser et al 2019;Vanderbosch et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The inclinations are also randomly selected from a Rayleigh distribution with σ = 1.12 • (Xie et al 2016). Choosing small but non-zero inclination angles is adequate for global stability studies (Veras et al 2018).…”
Section: Initial Orbitsmentioning
confidence: 99%
“…Regarding the inclination of the planet orbits, we have also randomly selected them from a Rayleigh distribution with σ = 1.12 • (Xie et al 2016). The choice of using small inclination angles is justified in this work since Veras et al (2018) concluded that near co-planar angles are adequate for global stability studies.…”
Section: Initial Orbitsmentioning
confidence: 99%